Expression of PSMD14 in lung adenocarcinoma and its impact on immune cell infiltration and prognosis: a comprehensive analysis based on RNA and single-cell RNA sequencing - Zhang, Jing; Sun, Bohao; Lai, Jiabin; Kong, Weike; Wang, Nan; Li, Panyuan; Wu, Yichen; Jiang, Zhaochang (Frontiers in Immunology, 2025)
BackgroundLung adenocarcinoma (LUAD) is distinguished by intricate relationships between tumor advancement and the immune microenvironment. The function of PSMD14 (Proteasome 26S Subunit, Non-ATPase 14) within the context of LUAD is not well elucidated, especially in terms of its correlation with immune cell infiltration and the prognosis of patients.MethodsThe objective of this research was to explore the expression levels of PSMD14 in LUAD and to evaluate its potential implications for tumor immunity and clinical outcomes. A multifaceted approach was adopted, which included the analysis of RNA sequencing (RNA-seq) data, assessment of immune cell infiltration, survival analysis, gene enrichment analysis, and integration of single-cell RNA-seq data to thoroughly evaluate the biological relevance of PSMD14. Furthermore, we examined the correlation between PSMD14 expression and clinical parameters. Immunohistochemistry techniques were employed to analyze PSMD14 expression in samples of invasive pulmonary adenocarcinoma.ResultsOur study demonstrated that the expression of PSMD14 is markedly elevated in LUAD and exhibits a positive correlation with other members of the JAMM family, including EIF3H and PSMD7. Importantly, elevated levels of PSMD14 were linked to poor patient prognosis, indicating its potential utility as a biomarker. Moreover, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that PSMD14 is significantly associated with pathways related to the cell cycle and nicotine dependence, underscoring its vital function in modulating cell proliferation and metabolic activities. Furthermore, PSMD14 expression was found to be associated with the infiltration of immune cells, particularly influencing T helper and Th2 cell populations, and exhibited an inverse relationship with several immune checkpoint molecules, such as PD-1 and TIGIT. Insights from single-cell RNA sequencing identified that PSMD14-expressing immune cell types in LUAD include dendritic cell (DC), monocytes, and tissue stem cells. These findings highlight the role of PSMD14 in the immune evasion strategies prevalent in LUAD. Additionally, a notable increase in PSMD14 protein levels was recorded in LUAD patients, with expression levels correlating with tumor size, lymph node involvement, and the TNM classification.ConclusionIn summary, our research underscores the crucial role of PSMD14 in LUAD, highlighting its promise as a potential target for therapy and a prognostic indicator. Furthermore, it opens up novel approaches for future therapeutic interventions.